KECERDASAN BUATAN DAN ORANG MUDA KATOLIK: TANTANGAN DAN PELUANG DI ERA DIGITAL - Monica Apriyani (Bahasa Indonesia, 2026)
This research presents an overview of artificial intelligence (AI) and its relationship with young people and the Catholic Church. AI has become an integral part of human life, increasingly integrated into daily routines, particularly among young people. The Catholic Church acknowledges and understands the rapid development of AI technology, recognizing it as both a challenge and an opportunity for the growth of young people's faith. This journal employs a literature review method, analyzing various books, articles, and academic journals that discuss artificial intelligence, youth, faith development, and the Church. Through this approach, the author identifies contemporary ideas that explore the relationship between young people and AI, as well as the appropriate attitudes to adopt in response to this phenomenon. Furthermore, the opportunities and challenges arising from the interaction between youth and AI are central to this study. As both the present and future of the Church, young people play a vital role in shaping the faith community. They are also the primary subjects of evangelization, being most directly exposed to AI technologies. The interaction between youth and AI within the context of Church life presents both opportunities and challenges. The convenience, speed, and broad reach offered by AI are seen as significant advantages. However, the reduction in direct interpersonal interaction poses a serious challenge, reflected in the decline of empathy, sensitivity, and awareness of surrounding social conditions. Therefore, the opportunities and challenges presented by AI in the lives of young people within the Church must be addressed wisely and appropriately to ensure that they contribute positively to the broader community.